Methodology of Islamic Psychotheraphy a Model of Islamic Psychotheraphy at Islamic Boarding School Suryalaya Tasik Malaya - Rajab, Khairunnas (Jurnal Usuluddin, 2010)
Islamic psychotherapy is a method based on al-Qur’an and alSunnah. al-Qur’an and al-Sunnah are source of knowledge. They contain methods for recovery, nurse, and treatment for human heart. The Suryalaya and inabah islamic boarding school have offered an islamic strengthening memory method through the thariqah qodiriyah naqsyabandiyah approach. This article aims to explain Islamic psychotherapy by giving an example of islamic psychotherapy practiced by the boarding school mentioned in this article